Applications of Quasigroups to Cryprography - Artamonov, V.A. (Sarajevo Journal of Mathematics, 2019)
The present paper contains a survey of some recent results on polynomially (functionally) complete quasigroups and their application obtained by joint Indo-Russian research group: S. Chakrabarti, S. Gangopadhyay, S. K. Pal, V.T.Markov.